2016
DOI: 10.18805/ag.v37i3.3538
|View full text |Cite
|
Sign up to set email alerts
|

Productive and reproductive perfomances of desi pigs: A review

Abstract: The assessment of productive and reproductive performances of pig breeds have been done in different countries of the world. However, the same study for indigenous or so called desi pigs in different parts of India is limited. It is now believed that the study of some productive and reproductive traits is most essential to evaluate the potentiality of these indigenous pigs. In India, only limited studies on productive and reproductive traits have been carried out on indigenous pigs that too detailed studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In this study, the CR values of (A 0 and B 0 ) and (A 2 and B 1 ) were better and in the excellent category than those of (A 1 and B 2 ), which were still considered unsatisfactory. Boro et al [23] stated that the conception rate using sexing semen reached 45%.…”
Section: Conception Rates Of Spermatozoa X-y Simmental Cattle On Bsa ...mentioning
confidence: 99%
“…In this study, the CR values of (A 0 and B 0 ) and (A 2 and B 1 ) were better and in the excellent category than those of (A 1 and B 2 ), which were still considered unsatisfactory. Boro et al [23] stated that the conception rate using sexing semen reached 45%.…”
Section: Conception Rates Of Spermatozoa X-y Simmental Cattle On Bsa ...mentioning
confidence: 99%
“…Only few references were available which grouped them into some population like Desi pigs of North India, Ankamali pigs of peninsular India, Gahuri pigs of Assam and Ghoongroo pigs of West Bengal (Bhat et al 1981, Bhat et al 2010). However, new population have been characterized and documented (Boro et al 2016a). Some of them have been found to be distinct and are registered by ICAR-NBAGR as new breeds of indigenous pigs.…”
Section: Breeds Of Indigenous Pigs Of Indiamentioning
confidence: 99%
“…Mishra et al (2009) reported that A1 allele had never been encountered in the eight buffalo breeds raised in India. In other words, A1 beta casein variant is generally found in European originated pure breeds or crossbreeds, and A2 beta casein variant is found in the native cattle and buffalo breeds of India and African domestic cattle (Ng-Kwai-Hang & Grosclaude, 2003;Boro et al 2016).…”
Section: Heredity Of A1 and A2 Milkmentioning
confidence: 99%